From epidemiology to public health decision making: analysis on IMD & vaccination strategy in Italy. (30th September 2020) - Igidbashian, S; Caracci, F; Bonanni, P; Castiglia, P; Conversano, M; Gabutti, G; Icardi, G; Lopalco, P L; Vitale, F; Checcucci Lisi, G
Abstract: Introduction: Invasive Meningococcal Disease (IMD) is one of the most severe vaccine-preventable disease, with high fatality rate and severe sequelae in up to 20% of survivors. MenB, MenC and MenACWY vaccines are available in Italy, but recommendations vary among Italian regions in terms of type of vaccines and targeted age groups. The aim of the study is to describe epidemiology of IMDs in order to provide the best vaccination strategy. Methods: IMDs surveillance data in the period 2011-2017 from the Italian National Health Institute were explored. Excel was used to present trend analysis, stratifying by age and serogroups. Results: In Italy, during the period 2011-2017, IMDs overall incidence increased from 0.25 cases/100, 000 inhabitants in 2011 to 0.33 in 2017. Most cases after 2013 were caused by non-B serogroups (52%, 52%, 66%, 64%, 59% from 2013 to 2017). Although incidence is highest in 1 years old children, the number of cases is highest in the age range 25-64. The number of cases in this age-range had a steady increase after 2013 (36 cases in 2011, 79 in 2017), with serogroups C, W and Y present in more than 65% of cases in 25+ age ranges after 2012. Conclusions: IMD is a rare but severe vaccine-preventable disease. The key role of public health is to monitor disease serogroups, trends and outbreaks and strengthen methodological evidence-based tools for decision-making processes, public health policies, planning of healthcare services and intervention measures, including immunization. The increase in incidence shown in the period 2011-2017 in Italy, although probably due to better surveillance, highlighted the high circulation also of non-B serogroups and the importance of the disease in the adult population. Based on our analysis we believe that anti-meningococcal vaccination plan in Italy should include the highest number of preventable serogroups and be aimed to the whole population through a multicohort strategy, including boosters in children and in adults. Key messages: Anti-meningococcal vaccination plan in Italy should include all the preventable serogroups and be aimed to the whole population with a multicohort strategy including boosters in children and in adults. The increase in incidence of IMD in the period 2011-2017 in Italy highlighted the high circulation also of non-B serogroups and the importance of the disease in the adult population.